The Effect of Public Awareness on the Islamic Financial Industry’s Development - Ernawati Ernawati; Rosnawintang Rosnawintang; Ambo Wonua Nusantara (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2022)
The development of Islamic finance is not related to the size of the Muslim population as a potential demand. Awareness is a crucial factor in the demand for Islamic banking services. This research investigates the effects of knowledge, regulation, and public awareness on Islamic finance development. This study considers awareness as the mediator variable of knowledge and regulation in supporting Islamic finance development. The study used secondary data published by ICD and Refinitiv, with data from 2013-2019 from 62 countries. Data were analyzed using panel data path regression. The research findings show that knowledge, regulation, and awareness significantly affect the development of the financial industry. The importance of awareness in promoting the Islamic financial industry is indicated by the positive and significant value of awareness as a mediator of knowledge and regulation. This study recommends the synergy between the government and Islamic financial education institutions in strengthening public awareness in encouraging the development of the Islamic finance industry through disseminating research results and government policies.How to Cite:Ernawati., Rosnawintang., & Nusantara, A. W. (2022). The Effect of Public Awareness on the Islamic Financial Industry’s Development. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 399-414. https://doi.org/10.15408/sjie.v11i2.25816.JEL Classification: D83, G18, G41